2015
DOI: 10.2217/fvl.15.23
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary Influenza Vaccines Against Avian Influenza in China

Abstract: Avian influenza (AI) is an infectious viral illness that affects numerous species of birds, including chickens, ducks, turkeys and geese. Poultry vaccination plays an important role for control of the AI virus and effectively prevents the infection in domestic chickens. However, new, increasingly virulent strains are constantly emerging, for which no vaccines are available. Avian influenza is also responsible for sporadically infecting humans and causing a wide range of clinical outcomes. Here, we review the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Over the course of 10 years, the control of H5N1 in China has required the introduction of seven different killed vaccines. In addition, H5N1 has also been combined with H9N2 for better vaccination coverage, adding two new killed vaccine formulations ( Fan et al ., 2015 ). In 2017, a vaccine combining H7N9 with H5N1 was approved for use in poultry ( Shi et al ., 2018 ).…”
Section: Ai Vaccines and Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the course of 10 years, the control of H5N1 in China has required the introduction of seven different killed vaccines. In addition, H5N1 has also been combined with H9N2 for better vaccination coverage, adding two new killed vaccine formulations ( Fan et al ., 2015 ). In 2017, a vaccine combining H7N9 with H5N1 was approved for use in poultry ( Shi et al ., 2018 ).…”
Section: Ai Vaccines and Vaccinationmentioning
confidence: 99%
“…In 2017, a vaccine combining H7N9 with H5N1 was approved for use in poultry ( Shi et al ., 2018 ). The need for the regular updating of H5N1 viral subtypes is also required for live recombinant NDV-vectored vaccines, with three different formulations (rLH5-1, rLH5-5 and rLH5-6) approved since 2005 ( Fan et al ., 2015 ). The need for regular updating of vaccinal strains was also reported by Tarigan et al .…”
Section: Ai Vaccines and Vaccinationmentioning
confidence: 99%
“…The H7N7 genotype was implicated in the 2003 epizootic in the Netherlands [ 19 ]. Over the past two decades, the H5N2 and H9N2 subtypes had been implicated in several outbreaks in China [ 10 ].…”
Section: Avian Influenza Viruses (Aivs)mentioning
confidence: 99%
“…Highly pathogenic AI (HPAI) viruses (HPAIVs) cause severe and fatal disease with up to 100% mortality in infected poultry [ 7 , 8 ]. Past epizootics such as those that occurred in Southeast Asia [ 9 ], China [ 10 ], and West Africa [ 8 ] had shown that even LPAI viruses such as H9N2 strains caused a mortality rate of up to 60 in affected chicken flocks [ 11 ]. The continued prevalence of these viruses in birds is inevitably threatening food security by lowering the production of poultry products for local consumption and export.…”
Section: Introductionmentioning
confidence: 99%
“…There have been cases of mass infection of livestock by malignant pathogens such as avian influenza (AI) [4] and foot and mouth disease (FMD). These pathogens are highly contagious and deadly to poultry and pigs [5,6], and can survive for a considerably long period at room temperature and even under sub-zero conditions [7]. Thus, it is of paramount importance to introduce and use appropriate management approaches to combat and to avoid the potential health risks derived from increasing concentration of livestock production and related concentration of livestock manure within a geographic area [7,8].…”
Section: Ofmentioning
confidence: 99%